Pengaruh Auditory Biofeedback dalam Meningkatkan Aktivasi Otot pada Latihan Beban - Fendy Nugroho; Aditya Johan Romadhon; Mashaf Fahrur Murdo Furqon (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: The use of biofeedback in training programs can provide direct visual or auditory feedback so that muscle activation needs can be monitored and maintained to produce more efficient muscle contractions. This makes energy use and contractions more selective in the muscles being trained. In addition, the use of biofeedback also provides motivation during exercise. Biofeedback can display changes in muscle activation patterns such as onset and peak contraction of several muscles during weightlifting. A common problem in weight training is the magnitude of co-contraction between agonist and antagonist muscles, which often leads to decreased energy efficiency and disrupted movement patterns, indicated by compensatory movements during lifting. Co-contraction of agonist and antagonist muscles is very high in beginners during weight training and decreases as motor control improves. Objectives: To determine the effect of using auditory biofeedback in increasing selective activation of the pectoralis muscle during dumbbell chest press weight training. Methods: The study design was a cross-sectional observation involving 50 adolescent subjects. Surface electromyography (sEMG) was attached to the pectoralis muscle to monitor muscle activation values during dumbbell chest press exercise. In the first session, the dumbbell chest press was performed without auditory feedback, but the sEMG remained attached and muscle activation results were monitored by the sEMG operator. In the second session, the dumbbell chest press was performed with auditory feedback. The results of pectoralis muscle activation based on sEMG recordings between exercises without and with auditory feedback were then compared. Results: The pectoralis muscle activation value during dumbbell chest press without auditory feedback had an average value of 63.38 ± 23.48 µV, whereas with auditory feedback the average was 82.55 ± 26.72 µV, with a significance value of p < 0.001. Conclusion: The average value of pectoralis muscle activation is higher when using auditory feedback compared to without it. Therefore, pectoralis muscle activation is greater when auditory feedback is used in weight training than without auditory feedback. Keywords: Auditory Biofeedback, Muscle Activation, Weight Training.